Feeling Heard and Not Judged: Perspectives on Substance Use Services Among Youth Formerly in Foster Care. (February 2018) - Braciszewski, Jordan M.; Tran, Tanya B.; Moore, Roland S.; Bock, Beth C.; Tzilos Wernette, Golfo K.; Chamberlain, Patricia; Stout, Robert L.; Vose-O'Neal, Adam
Youth in foster care have limited access to substance use services for a variety of reasons. Attempts to unpack this health disparity have focused on foster care systems, administrators, providers, and foster parents. This study seeks to understand the perspectives of youth themselves, with the hope of understanding their experiences with and preferences for such services. Analyses of focus groups with youth who had recently left foster care suggested concrete and perceptual facilitators/barriers to treatment. Concrete facilitators/barriers included the need for expanding social support, access to multiple service options, and tailored intervention approaches. Perceptual concerns revolved around understanding each individual's readiness to change, feeling judged by authority figures, and desiring help from people with lived experience. Participants also described novel intervention ideas, including a focus on technology-based approaches. By relying on youth voices, we can improve upon the current state of substance use interventions within foster care.